Handbook of research on nature inspired computing for economics and management - Rennard Jean-Philippe (Hershey PA : Idea Group Reference, 2007)
'This book provides applications of nature inspired computing for economic theory and practice, finance and stock-market, manufacturing systems, marketing, e-commerce, e-auctions, multi-agent systems and bottom-up simulations for social sciences and operations management'--Provided by publisher
Vol. 1. Chapters I-XXVI - vol. II. Chapters XXVII-LVIII
Keywords: Economics -- Data processing; Economics, Mathematical; Management -- Data processing; Evolutionary computation; Evolutionary programming (computer science)